2020
DOI: 10.1111/ejn.14911
|View full text |Cite
|
Sign up to set email alerts
|

Neural coordination of bilateral power and precision finger movements

Abstract: The phylogenetic development of upper extremities for other tasks than locomotion represents the basis for the cultural achievement of human beings (Herder, 1785). Upright stance and gait allow the use of hands and fingers to perform a wide variety of voluntarily controlled tasks used in activities of daily life (ADL) or for cultural purposes. In most frequently performed ADL movements fingers act as part of the hand, that is, hand and fingers operate as a unity. This group of motor tasks comprises, for exampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…We did not study fine-motor control because many stroke patients are not capable of generating independent finger movements. However, it is important to note that there are neurophysiological and neuroanatomical differences in the control of bilateral proximal limb-coordination vs. bilateral distal-limb coordination [ 56 ]. For example, electrical stimulation to forearm muscles on one limb during bilateral hand movement resulted in muscular responses in both limbs, whereas stimulation to one finger during bilateral finger movement resulted in responses only in the stimulated finger.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not study fine-motor control because many stroke patients are not capable of generating independent finger movements. However, it is important to note that there are neurophysiological and neuroanatomical differences in the control of bilateral proximal limb-coordination vs. bilateral distal-limb coordination [ 56 ]. For example, electrical stimulation to forearm muscles on one limb during bilateral hand movement resulted in muscular responses in both limbs, whereas stimulation to one finger during bilateral finger movement resulted in responses only in the stimulated finger.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the human bilateral movement repertoire is very broad, and there exist many other patterns apart from the cyclical rhythmical pattern tested here. Some may be asymmetrical and more complex (such as playing the piano), and some may not be rhythmic (such as opening a bottle) [ 56 ]. Another limitation is that we only included participants who were right-handers before stroke.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Park et al (2021) compared digital trail-making-test performance while walking before and after exercise to determine neural correlates of improved performance. In the review paper by Dietz (2020), studies investigating neural coordination of bilateral power and precision finger movements are discussed.…”
Section: Cognitive Control Of Actionmentioning
confidence: 99%
“…For instance, in a published study [15], Grigorev et al showed that vibrotactile feedback was useful to increase corticospinal excitability in hand muscles during motor imagery with an ERD-based BCI system. Moreover, Dietz et al proposed an ERD-based brainmachine interface to work effectively in the clinical recovery of functional movements [16]. Consistent with these studies, the physiological characteristics of ERD have been used as EEG markers in an online BCI system in the last few decades.…”
Section: Introductionmentioning
confidence: 97%